Effective Communication in the Workplace : Learn How to Communicate Effectively and Avoid Common Barriers to Effective Communication - Gutierez, Anthony ([CreateSpace Independent Publishing Platform], 2017)
Among the crucial ingredients to a business’s success is effective workplace communication. It is, therefore, unfortunate that effective communication does not happen smoothly in many companies. Ineffective communication in the workplace is one of the leading reasons why many businesses lose profits and valuable resources, including excellent employees and clients. Companies can miss important opportunities to grow and expand their business when there is poor communication in the workplace. Whether a business is big or small, management must invest time and money to develop, practice and improve communication skills. People often take effective communication in the workplace for granted, but wiser entrepreneurs recognize that there is a great benefit and much power in the ability to communicate effectively inside the workplace. Messages are clearer and productivity is higher when there is no miscommunication between the employer and the employee, between the workers, and between the people in management positions. This book is designed to enlighten business owners, managers, supervisors, and employees about the barriers of effective communication in the workplace, what causes them, and how they can be overcome. Reading this book will also help you learn how to effectively deliver your message to your boss, workers, or colleagues for greater productivity, cooperation, and understanding